2018
DOI: 10.11606/issn.2317-0190.v25i2a162566
|View full text |Cite
|
Sign up to set email alerts
|

Perfil da resiliência em indivíduos com amputação de membro inferior

Abstract: Objetivo: Identificar o perfil sociodemográfico dos amputados de membro inferior bem como, os níveis e os fatores da resiliência. Método: Trata-se de um estudo descritivo, quantitativo e transversal. Os dados foram coletados através de um questionário semiestruturado após aprovação pelo Comitê de Ética e Pesquisa. O período de coleta foi entre Setembro a Novembro de 2017 no ambulatório do Centro Estadual de Reabilitação e Readaptação de Goiânia – Goiás. Os dados foram apresentados em frequências, média e desvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…Koivunen et al reported that a person who underwent lowerlimb amputation experienced functional, psychological, and social changes, with a significant impact on quality of life (3) . Amputation leads to functional limitations that include dependence on daily living activities, changes in balance, decreased mobility, and an increased likelihood of permanent disability (4) . The loss of physical, psychological, or intellectual autonomy caused by disease and worsened by the amputation makes it impossible for the person to perform daily life activities independently, thus compromising self-care and making them dependent on someone to perform their daily life activities (5) .…”
Section: Introductionmentioning
confidence: 99%
“…Koivunen et al reported that a person who underwent lowerlimb amputation experienced functional, psychological, and social changes, with a significant impact on quality of life (3) . Amputation leads to functional limitations that include dependence on daily living activities, changes in balance, decreased mobility, and an increased likelihood of permanent disability (4) . The loss of physical, psychological, or intellectual autonomy caused by disease and worsened by the amputation makes it impossible for the person to perform daily life activities independently, thus compromising self-care and making them dependent on someone to perform their daily life activities (5) .…”
Section: Introductionmentioning
confidence: 99%
“…As muletas são dispositivos auxiliares em que uma pessoa com dificuldade em sua mobilidade é apoiada ao nível dos braços e ombros para aliviar a carga do corpo sobre os membros inferiores, seja em movimento ou em repouso (Carvalho, 2013;Paz, et al, 2018). Com o passar dos tempos, as muletas têm sido um elemento primordial na assistência da locomoção de pessoas, eventualmente, estes sujeitos apresentam um determinado tipo de incapacidade motora dos membros inferiores.…”
Section: Introductionunclassified